Impact of n-type versus p-type doping on mechanical properties and dislocation evolution during SiC crystal growth - Wellmann, Peter; Hens, Philip; Sakwe, Aloysius; Queren, Desiree; Müller, Ralf; Durst, Karsten; Göken, Mathias (Materials Science Forum, 2007)
The origin of dislocation evolution during SiC crystal growth is usually related to lattice relaxation mechanisms caused by thermal stress. In this paper we discuss dislocation generation and dislocation propagation related to doping and suppression of basal plane dislocations, the latter being of particular interest for bipolar electronic devices. We have prepared alternating p-/n-/p-doped SiC crystals using the donor nitrogen and the acceptors aluminum or boron. In addition we determined the mechanical properties of n-type and p-type SiC; in particular we measured the critical shear stress by nano-indentation on c-plane and a-plane 6H-SiC surfaces. A considerably lower basal plane dislocation density is found in aluminum as well as in boron doped p-type SiC compared to nitrogen doped n-type SiC. It is concluded that the explanation of the reduced basal plane dislocation density in p-type SiC needs the consideration of electronic as well as mechanical effect
Keywords: Basal Plane Dislocation (BPD); Doping; PVT Growth; SiC